Pengaruh Good Corporate Governance Terhadap Praktik Manajemen Laba Riil Pada Perusahaan Manufaktur - Ery Hidayanti; Ratna Wijayanti Daniar Paramita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2014)
Principles of Good Corporate Governance ( GCG ) as a new paradigm which state has four main components to improve the professionalism and Welfare holders of the issued and paid new article without prejudice to the interests of stakeholders . Yet the implementation of GCG mechanism new article posted by Its Good , Its can trigger to remove information. That gave a negative effective on the issued and paid the price list , Therefore posted issued and paid-holder must be able to supervise the management, running his company . The GCG implementation in Indonesia becoming less maximum company weakness and lead to a prolonged crisis . Research purposes is to determine empirically whether corporate governance practices affect the real. Management Delta Company The manufacturing in IDX . Husband is a causality Research new articles using multiple linear regression analysis as a tool , new articles purposive sampling technique as a determinant of the sample . Research The results showed that the only variable The managerial ownership has an influence on management practices in real delta, The Company The article indicated the significance of the new notes small more language of 0.05.